AB0062 CHARACTERIZATION OF IL-12 AND IL-23 REDUCTION BY TOFACITINIB IN MDCS. (2nd June 2020) - Vincken, N.; Angiolilli, C.; Cardoso, S.; Lopes, A.; Olde-Nordkamp, M.; Radstake, T.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory auto-immune disease characterized by an excessive production of pathogenic mediators that cause inflammation of the skin, peripheral joints, entheses and the spine. Among these, interleukin (IL)-23, IL-12, the IL-17 family and TNF constitute key players in PsA pathogenesis. 1, 2 IL-23, consisting of IL23A (IL-23p19) and IL12B (IL-12p40) subunits, is predominantly produced by myeloid dendritic cells (mDCs). While the p19 subunit is unique to IL-23, the p40 subunit is shared with IL-12. Together, IL-12 and IL-23 play a crucial role in promoting the differentiation of naïve T lymphocytes into T helper (Th) interferon (IFN)-γ-producing Th1 or IL17-producing Th17 cells, respectively. 3 Small-molecule inhibitors, such as the JAK/STAT inhibitor Tofacitinib, have recently shown promising therapeutic potential in PsA clinical trials. 4 The inhibition of JAKs by Tofacitinib results in the direct suppression of multiple intracellular signaling pathways which constitute key hubs in the cytokine network. 5 However, whether Tofacitinib is able directly target IL-12/IL-23 production by mDCs has not yet been documented. Suppression of these canonical inflammatory pathways would provide further evidence that Tofacitinib is an effective drug in halting both innate and adaptive immune responses. Objectives: To evaluate the transcriptional and molecular events underlining IL-12 and IL-23 regulation by Tofacitinib in mDCs. Methods: Peripheral blood mononuclear cells from healthy donors were isolated by Ficoll gradient. Monocytes and myeloid dendritic cells (mDCs) were isolated by using magnetic beads on autoMACS. Monocytes were cultured for 6 days in the presence of IL-4 and granulocyte-macrophage colony-stimulating factor (GM-CSF) to generate monocyte-derived dendritic cells (moDCs). MoDCs were harvested, washed and put to rest for 1 day prior to stimulation, while mDCs were stimulated on the same day of isolation. Both moDCs and mDCs were pre-treated with Tofacitinib and then stimulated with either lipopolysaccharide (LPS) or combination of LPS with IFN-γ for 4 hours. Cytokines were measured using enzyme-linked immunosorbent assay (ELISA) and gene expression was assessed using quantitative polymerase chain reaction (qPCR). Results: Treatment of both mDCs and moDCs with Tofacitinib led to a decreased mRNA expression of IL-12 p40 ( IL12B ) in the presence of TLR4 and IFNγ co-stimulation. The decreased IL12B mRNA expression also resulted in lower production of IL-12 p40 and IL-23 proteins in mDCs. Conclusion: In this work, we demonstrated for the first time that Tofacitinib can suppress the production of IL-23/IL-12 p40 subunit in mDCs, upon the condition that an active type II IFN signalling is also present in these cells. This observation indicates that specific factors, such as endogenous IFN-γ levels in the serum of PsA patients, can possibly predict differential responses to Tofacitinib treatment. References: [1]Gaffen SL. et al. The IL-23-IL-17 immune axis: from mechanisms to therapeutic testing. Nat Rev Immunol. 2014 Sep;14(9):585-600 [2]Bravo A, Kavanaugh A. Bedside to bench: defining the immunopathogenesis of psoriatic arthritis. Nat Rev Rheumatol. 2019 Nov;15(11):645-656 [3]Floss DM. et al. Insights into IL-23 biology: From structure to function. Cytokine Growth Factor Rev. 2015 Oct;26(5):569-78 [4]Berekmeri A. et al. Tofacitinib for the treatment of psoriasis and psoriatic arthritis. Expert Rev Clin Immunol. 2018 Sep;14(9):719-730 [5]T Virtanen A. et al. Selective JAKinibs: Prospects in Inflammatory and Autoimmune Diseases. BioDrugs. 2019 Feb;33(1):15-32 Disclosure of Interests: None declared